CHARACTERISTICS OF CHANGES IN BLOOD PRESSURE AND HEART RHYTHM DISTURBANCES IN PATIENTS WITH METABOLIC SYNDROME - A. H. Mustafayeva (Евразийский Кардиологический Журнал)
The purpose of this work is to analyze the daily levels of blood pressure and heart rate variability in patients with signs of metabolic syndrome.Materials and methods. In the period from 2013 to 2016, 364 patients of the age from 20 to 80 (200 men and 164 women) with newly diagnosed MS were prospectively examined. Daily ECG monitoring applying the Holter method was performed with the help of Cardiomax system (USA), in compliance with the standard method for diagnosing paroxysmal forms of arrhythmia and stress and painless forms of ischemia. V2, V5 and avF derivations were registered.Results. The maximum daily average values of systolic and diastolic blood pressure recorded in patients of the 61 to 80 age group were the following: systolic BP - 156.9±3.5 mm Hg diastolic BP - 96.2±4.1 mm Hg The heart rate variability analysis showed that the value of circadian index in patients of the third age group was significantly lower (1.14±0.12) than in patients of the first and second groups, amounting to respectively 1.2±0.11 and 1.19±0.13. Besides, we noticed an increase of daytime and night Ps levels (up to 79.0±9.0 and 66.5±4.1 BPM) in patients of the second group compared to the first group, where the values of these indicators were respectively 75.4±8.4 and 60.6±6.2 BPM. Heart rate variability at different times of day depending on age indicate adverse changes in the autonomic regulation of cardiac activity alongside with increasing the age of patients with MS. With the increase of age in patients with Ms, the rate of detecting cardiovascular complications risk factors steadily grows.Conclusion. It is necessary to conduct dynamic monitoring for patients with symptoms of metabolic syndrome in order to identify signs of cardiovascular system state disturbances, blood pressure and heart rate in particular.